ANALISIS PERILAKU HIDUP SEHAT PESERTA DIDIK KELAS X SMK NEGERI 7 PONTIANAK - Sri Ambar Wati; Yuline Yuline; Indra Astuti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to determine how to maintain reproductive health and the risks of reproductive health of students as well as what efforts are made by guidance and counseling teachers in helping healthy living behavior, especially student reproductive health. The research method used is descriptive in the form of survey research. The research was conducted in class X SMK Negeri 7 Pontianak. The population in this study amounted to 338 students. The sample in this study used saturated sampling or census, the sample amounted to 286 students. The data collection technique is indirect communication, and the data collection tool is a questionnaire. The results showed that students in class X SMK Negeri 7 Pontianak in how to maintain reproductive health were classified as "good" with a percentage of 79.47552%, and students in understanding the risks of reproductive health were classified as "good" with a percentage of 79.21329%. , as well as the efforts made by guidance and counseling teachers in helping healthy living behavior, especially the reproductive health of students classified as "good" with a percentage of 79.80769%.Keywords: Counseling, Guidance, Health, Healthy Living, Reproduction and Students